(untitled) (Conference Zone, 2022)
Mannequins over the past hundred and fifty years have evolved from a simple "hanger" for clothes into spectacular figures for its demonstration. Every self-respecting owner of a large chain of stores orders individual mannequins that will reflect the concept of the company. And they do it for a reason, because, according to research, the presence of such a presentation of the product increases sales up to four times. The demand for mannequins is due not only to the desire to show your brand, but also to a short shelf life, which is only a year. The business of making mannequins is considered costly and time-consuming, if only because high-quality samples are made by hand. Consequently, a large number of employees are required. But, nevertheless, such a case attracts Russian businessmen: the market is saturated with foreign-made mannequins, which allows you to find your niche at least at the local level. [1-20] All mannequins are divided into two large groups: male and female. But there are also many types that differ in purpose, appearance and shape.